Pengaruh Penggunaan Geogebra Terhadap Kemampuan Pemecahan Masalah Matematis Ditinjau dari Self-Efficacy Siswa - Hermawan, Toto; Santoso, Fattah Setiawan; Putra, Aji Permana (Indo-MathEdu Intellectuals Journal, 2025)
Mathematical problem-solving skills are an important aspect of learning mathematics. One of the factors that affect this ability is self-efficacy in completing academic tasks. As technology has evolved, the use of interactive software such as GeoGebra has been widely used in math learning. This study aims to analyze the influence of the use of GeoGebra on the mathematical problem-solving ability of junior high school students from the level of self-efficacy. The approach used is quantitative descriptive. The population in this study is all grade VIII students at MTs Negeri 1 Yogyakarta, with a sample of 32 students from class VIII C who were selected using purposive sampling techniques. The data collection technique used is through a problem-solving test. This study applies the one-group pretest-posttest design. The data analysis used was a simple linear regression analysis. The results of data analysis showed that the use of GeoGebra had a significant influence on improving students' mathematical problem-solving skills based on the level of self-efficacy